A Finite Element Analysis-Based Modeling and Evaluation Method for Sternum Support Brace - Linhua Lv; Junyi Hu; Wanquan Liu; Jianqing Peng (IEEE Access)
Sternum support braces are commonly used in thoracic surgery to secure the chest after open chest procedures. Despite their widespread use in postoperative recovery, current modeling and performance evaluation methods have significant limitations that hinder the optimization and improvement of sternum support braces. To address these challenges, this study proposes a finite element analysis-based method for modeling and evaluating sternum support braces. First, a 3D model of the brace was constructed using 3D scanning technology, followed by mathematical modeling using the finite element method. Subsequently, the factors affecting users’ experience with sternum support braces were analyzed. Three quantitative indicators were designed to scientifically assess brace performance. Finally, four commonly used sternum support braces were selected as examples for simulation modeling, performance evaluation, experimentation, and surveys to validate the effectiveness of the proposed method. The findings demonstrate that this method effectively addresses the difficulties in measuring the pressure exerted by sternum support braces and in quantifying their performance. It offers a simple and accurate means of evaluating the performance of sternum support braces, and the evaluation results align closely with patients’ actual experiences and needs. This method provides a scientific basis for further optimization of design and clinical applications.